2012
DOI: 10.1186/gb-2012-13-10-r98
|View full text |Cite
|
Sign up to set email alerts
|

CHANCE: comprehensive software for quality control and validation of ChIP-seq data

Abstract: ChIP-seq is a powerful method for obtaining genome-wide maps of protein-DNA interactions and epigenetic modifications. CHANCE (CHip-seq ANalytics and Confidence Estimation) is a standalone package for ChIP-seq quality control and protocol optimization. Our user-friendly graphical software quickly estimates the strength and quality of immunoprecipitations, identifies biases, compares the user's data with ENCODE's large collection of published datasets, performs multi-sample normalization, checks against quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 11 publications
2
58
0
Order By: Relevance
“…We confirmed the quality of the ChIP-seq data with CHANCE (Supplemental Fig. S9; Diaz et al 2012). In addition, we found that 51%-55% of GBM H3K4me3 peaks overlap with the ChromHMM promoter state in at least one of the nine ENCODE cell lines analyzed in Ernst et al (2011) (Supplemental Fig.…”
Section: Acquisition Of H3k4me3 In Primary Gbm At a Subset Of Recurresupporting
confidence: 54%
See 1 more Smart Citation
“…We confirmed the quality of the ChIP-seq data with CHANCE (Supplemental Fig. S9; Diaz et al 2012). In addition, we found that 51%-55% of GBM H3K4me3 peaks overlap with the ChromHMM promoter state in at least one of the nine ENCODE cell lines analyzed in Ernst et al (2011) (Supplemental Fig.…”
Section: Acquisition Of H3k4me3 In Primary Gbm At a Subset Of Recurresupporting
confidence: 54%
“…The sequencing libraries were aligned as single-end samples to ensure equal mapping bias across the samples. ChIP enrichment was further verified using CHANCE (Diaz et al 2012). Peak calling was performed using MACS at a 1% false discovery rate and a P-value < 1 3 10 À10 ).…”
Section: Chromatin Immunoprecipitation-sequencing (Chip-seq)mentioning
confidence: 99%
“…Quality control of the Nano-ChIP-seq data was performed using two independent methods: ChIP enrichment at known promoters and employing the ChIP-seq quality control and validation tool ChIP-seq analytics and confidence estimation (CHANCE; ref. 41). Comparisons of Nano-ChIP-seq read densities at 1,000 promoters associated with highly expressed protein-coding genes confirmed successful enrichment in all H3K27ac and H3K4me3 libraries.…”
Section: Identifying Epigenomic Promoter Alterations In Gastric Cancermentioning
confidence: 71%
“…Only tags that passed the quality filter and mapped uniquely to the genome were used. ChIP enrichment was further verified using CHANCE (58). The H3K4me3 mark peaks were identified using MACS 2.0.1 (59) with two biological replicate samples, including corresponding input, shift-size window 73 bp, no model, with P -value threshold <10E−5.…”
Section: Methodsmentioning
confidence: 99%